Culture changes among the matigsalogs in the lumads-dev area in Malabog, Paquibato District, Davao City - Avila, Ava Patricia C.
This study tells of the cultural changes that the Matigsalogs of the Livelihood for a United Matigsalogs' Determination towards Sustainable Development (LUMADS-DEV) in Malabog, Paquibato District, Davao City went through. The study aims to describe the lifestyle of the Matigsalog community both then and now as they were influenced by external forces and how these forces affected them and their way of life. Agents such as the illegal loggers, the Hijas de Jesus sisters and the Bisaya settlers brought changes to the Matigsalog group. Contact with outsiders brought both positive and negative changes. While the illegal loggers bribed their way into their land leaving the forest barren, the Hijas de Jesus later conducted livehood programs to uplift economic condition. Slowly, they have gained confidence and achieved sustenance through active participation self-reliance and growth productivity. Amidst the economic progress they are gaining still, depressing encounters do occur like unpredictable weather phenomenon. Also the inevitable pull of city ways that have attracted many of the younger generation influenced by some Bisaya settlers. Since climate conditions are unavoidable,they tried to live with it. However, the influence of the Bisaya settlers and inevitable fascination by the youth with modern ways today, prompted the old Matigsalogs to plan on building a school to preserve their living traditions. This study discusses the life of the Matigsalogs today, particularly illustrating the lifestyle and sime ways of city-life combined.
Thesis, Undergraduate (BA Social Science) -- U. P. in Mindanao